IN THEORETICAL MECHANICS, THE ISSUE OF USING A SOFTWARE TOOL TO EXPRESS THE RELATIONSHIP BETWEEN THE CYLINDRICAL COORDINATE SYSTEMAND THE DEKART COORDINATE SYSTEM (Web of Discoveries: Journal of Analysis and Inventions, 2024)
In this work, the problem of increasing students' mastery of the relationship between the cylindrical coordinate system and the dekart coordinate system have been studied. It has been studied that expressing the relationship between coordinates with the help of software is effective in increasing the mastery rate. The importance of improving basic competence of students has been discussed in the course of theoretical mechanics. The matter of how important the use of software training tools in improving basic competence is has been outlined.